2008
DOI: 10.1182/blood-2007-03-081018
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma in patients younger than age 50 years presents with more favorable features and shows better survival: an analysis of 10 549 patients from the International Myeloma Working Group

Abstract: We analyzed the presenting features and survival in 1689 patients with multiple myeloma aged younger than 50 years compared with 8860 patients 50 years of age and older. Of the total 10 549 patients, 7765 received conventional therapy and 2784 received high-dose therapy. Young patients were more frequently male, had more favorable features such as low International Staging System (ISS) and Durie-Salmon stage as well as less frequently adverse prognostic factors including high C-reactive protein (CRP), low hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
3
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 27 publications
10
154
3
8
Order By: Relevance
“…A more recent retrospective study did analyze patients under 50 years of age. 8 This study showed a better outcome for young patients when treated with standard doses of chemotherapy, but not if treated with high-dose melphalan.…”
Section: Discussionmentioning
confidence: 84%
“…A more recent retrospective study did analyze patients under 50 years of age. 8 This study showed a better outcome for young patients when treated with standard doses of chemotherapy, but not if treated with high-dose melphalan.…”
Section: Discussionmentioning
confidence: 84%
“…The 5-year relative survival rate for MM is around 35%. Survival is higher in younger people and lower in the elderly (Bergsagel et al 1979and Rodon 2002and Ludwig et al 2008. Relevant demographic studies of MM pertaining to our country are not available except for few sporadic cross sectional studies (Kibria et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Markov state transition probabilities of moving from one health state to another were computed using date on progression free survival, while the probability to die due to multiple myeloma was computed using the overall survival [18,19].…”
Section: Clinical and Epidemiological Parametersmentioning
confidence: 99%